Generation Z Muslim Consumers And The Fomo Trend Of Non-Halal Korean Food In Indonesia: A Sharia Perspective Study - DAULAY, ULAN DARI; Poppy Wulandari; Nurfhatih Hayati Zukrufa (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2025)
Abstract This research examines the problematic of fomo in consuming Korean food. This research also examines how Islam views the fomo trend of non-halal Korean food among Indonesian Muslims, as well as the essence of halal food for sharia compliance by a Muslim, how the role of importers in distributing Korean food to Indonesia. The benefit obtained from the results of this study is that it can provide an in-depth understanding based on a sharia perspective regarding the fomo trend among Indonesian Muslims in consuming Korean food. This research uses qualitative methods and is described descriptively with data sources based on library research or literature studies from various literatures, which aim to review and evaluate relevant research so as to provide a point of view that can answer research problems. The FOMO trend has an unfavorable impact on individual social activities on social media, with various types of food entering Indonesia whose halalness is unclear. As a devout Muslim, it is necessary to be aware of the importance of the halalness of the food consumed. Based on the analysis and findings of the researchers, several findings can be concluded, namely: The importance of Sharia compliance for a Muslim; Consumer awareness of halal food; The role of Importers and Halal Certification Organizing Bodies for non-halal products circulating in the market. Keywords: halal sertification, fomo trend, muslim consumers, korean food, importir. Abstrak Penelitian ini mengkaji problematika tren fomo dalam mengkonsumsi makanan Korea. Penelitian ini mengkaji bagaimana pandangan Islam terhadap tren fomo makanan Korea non halal di kalangan muslim Indonesia, serta esensi makanan halal bagi kepatuhan syariah oleh seorang muslim, dan peran importir dalam mendistribusikan makanan Korea ke Indonesia. Penelitian ini memberikan pemahaman yang mendalam tentang konsumsi seorang muslim dalam menghadapi tren fomo makanan Korea berdasarkan perspektiv syariah. Penelitian ini menggunakan metode kualitatif dan diuraikan secara deskriptif dengan sumber data dari dari berbagai literatur dengan tujuan untuk mengkaji dan mengevaluasi penelitian yang relevan sehingga memberikan sudut pandang dalam menjawab permasalahan penelitian. Tren FOMO memberikan dampak yang kurang baik bagi aktivitas sosial individu di media sosial, dengan adanya berbagai macam jenis makanan yang masuk ke Indonesia yang belum jelas kehalalannya. Sebagai konsumen muslim, perlu adanya kesadar akan pentingnya kehalalan makanan yang dikonsumsi. Berdasarkan analisis dan temuan peneliti, maka dapat disimpulkan beberapa temuan yaitu: Pentingnya kepatuhan Syariah bagi seorang muslim; Kesadaran Konsumen akan makanan halal; Peran Importir dan Badan Penyelenggara Sertifikasi Halal atas produk-produk non halal yang beredar di pasar. Kata Kunci: sertifikasi halal, tren fomo, konsumen muslim, makanan korea, importir